Bone Marrow Mesenchymal Stem Cell Transplantation Retards the Natural Senescence of Rat Hearts. (8th April 2015) - Zhang, Mingyu; Liu, Di; Li, Shuang; Chang, Lingling; Zhang, Yu; Liu, Ruixue; Sun, Fei; Duan, Wenqi; Du, Weijie; Wu, Yanping; Zhao, Tianyang; Xu, Chaoqian; et al.
Abstract: : Bone marrow mesenchymal stem cells (BMSCs) have been shown to offer a wide variety of cellular functions including the protective effects on damaged hearts. Here we investigated the antiaging properties of BMSCs and the underlying mechanism in a cellular model of cardiomyocyte senescence and a rat model of aging hearts. Neonatal rat ventricular cells (NRVCs) and BMSCs were cocultured in the same dish with a semipermeable membrane to separate the two populations. Monocultured NRVCs displayed the senescence-associated phenotypes, characterized by an increase in the number of β-galactosidase-positive cells and decreases in the degradation and disappearance of cellular organelles in a time-dependent manner. The levels of reactive oxygen species and malondialdehyde were elevated, whereas the activities of antioxidant enzymes superoxide dismutase and glutathione peroxidase were decreased, along with upregulation of p53, p21 Cip1/Waf1, and p16 INK4a in the aging cardiomyocytes. These deleterious alterations were abrogated in aging NRVCs cocultured with BMSCs. Qualitatively, the same senescent phenotypes were consistently observed in aging rat hearts. Notably, BMSC transplantation significantly prevented these detrimental alterations and improved the impaired cardiac function in the aging rats. In summary, BMSCs possess strong antisenescence action on the aging NRVCs and hearts and can improve cardiac function after transplantation in aging rats. The present study, therefore, provides an alternative approach for the treatment of heart failure in the elderly population. Significance: This study demonstrates that bone marrow mesenchymal stem cells show antisenescence action on aging neonatal rat ventricular cells and heart and improve cardiac function in aging rats. The results provide a novel strategy for retarding the cardiac aging process in physiology and abnormal conditions or pathology. This study also provides an alternative approach for treatment of heart failure in the elderly population. Abstract : This study investigated the antiaging properties of bone marrow mesenchymal stem cells (BMSCs) and the underlying mechanism in a cellular model of cardiomyocyte senescence and a rat model of aging hearts. BMSC transplantation significantly prevented detrimental alterations and improved the impaired cardiac function in the aging rats. The present study therefore provides an alternative approach for the treatment of heart failure in the elderly population.